2020
DOI: 10.1063/5.0011380
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of substrate roughness on the local glass transition of polystyrene

Abstract: Numerous computer simulations have shown that local dynamics associated with the glass transition can be slower next to rough interfaces compared with smooth interfaces. Even though the impact of surface roughness has been frequently considered computationally and theoretically, almost no experimental studies exist investigating these effects. Using a hydrogen fluoride vapor treatment, we created silica substrates with an increase in roughness that left the surface chemistry unchanged. The local glass transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…In comparison with bulk films of the same polymer, thin films of linear, freely deposited polymers that are a few tens of nanometers thick may exhibit significantly different properties, for example, glass transition temperature ( T g ), fragility, and stiffness among others. [ 1–48 ] For instance, in comparison with a bulk polystyrene (PS) film and as measured by ellipsometry, a 21‐nm‐thick, substrate‐supported high molecular weight (MW) PS film exhibits a T g reduction of 10°C. [ 18 ] Understanding such nanoscale T g ‐confinement effects in polymers is important for many advanced technological applications, for example, thin films used in nanolithography processes for microchip manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with bulk films of the same polymer, thin films of linear, freely deposited polymers that are a few tens of nanometers thick may exhibit significantly different properties, for example, glass transition temperature ( T g ), fragility, and stiffness among others. [ 1–48 ] For instance, in comparison with a bulk polystyrene (PS) film and as measured by ellipsometry, a 21‐nm‐thick, substrate‐supported high molecular weight (MW) PS film exhibits a T g reduction of 10°C. [ 18 ] Understanding such nanoscale T g ‐confinement effects in polymers is important for many advanced technological applications, for example, thin films used in nanolithography processes for microchip manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…17 More recent work has identified that chain connectivity across the interface appears to play a dominant role, 27 as opposed to interfacial roughness. 28 T g (z) of a thin pyrene-labeled PS probe layer placed at a distance z from the PS/PDMS interface. These findings demonstrate that the breadth of the compositional interface between the two dissimilar polymers and the modulus of the neighboring domain are key factors controlling the T g (z) behavior, providing insight for related theoretical efforts in the field 1,8,13,14,29−34 into the control parameters responsible for this phenomenon.…”
mentioning
confidence: 99%
“…In follow-up work, we were able to show that chain connectivity plays a dominant role in this behavior, 27 while interface roughness has little to no impact. 28 However, it is worth noting that, although chain connectivity across the interface itself seems to be important to at least create interfacial breadth, we are observing significant shifts in local T g (z) at distances z sufficiently far away from the interface that no individual chain can span the distance. Shown in Supporting Information, we demonstrate how the T g (z = 50 nm) decrease develops upon annealing of the PS/PDMS interface at 140 °C, requiring 60−90 min to reach equilibrium.…”
mentioning
confidence: 99%
“…This generally valid idea is a good starting point in probing the structure–dynamics relation in polymer nanocomposites and films. However, due to the large number of the parameters affecting the properties and the experimental challenges related to the sample preparation [ 8 , 9 , 10 ], which in part stem from the irregularity of the surface [ 11 , 12 , 13 , 14 ], many essential theoretical questions remain to be addressed [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by a recent experimental interest in rough surfaces [ 11 , 12 , 13 , 14 ], we aim to provide a detailed analysis of the structure–dynamics relation in hybrid polymer-based materials with irregular interfaces. More specifically, we employ an atomistic molecular dynamics simulation technique to study a realistic model of cis -1,4-polybutadiene chains in melt adsorbed on an amorphous silica slab.…”
Section: Introductionmentioning
confidence: 99%